Integrated Hajj Computerization System (SISKOHAT) And E-Government At The Office Of The Ministry Of Religion Of Cirebon City - Fajru Sobah, Ayis; Vanesavirgi, Vanesavirgi; Zulkarnaen, Iskandar (Jurnal Polisci, 2025)
Background. This research is based on the problem formulated in the problem statement, namely the Implementation of E-Government Through the Integrated Hajj Computerization System, abbreviated as SISKOHAT. Hajj services at the Cirebon City Ministry of Religion Office have yet to reach an optimal level. Aims. This problem causes network disruptions in the system, difficulties with registration and input for elderly pilgrims, a lack of discipline among several employees, limited facilities with only one SISKOHAT room, and data inconsistencies in the Hajj registration requirements documents. Therefore, the researcher, who has observed the Implementation of E-Government through the Integrated Hajj Computerization System, SISKOHAT, is interested in taking the title. Methods. This research uses a qualitative approach, data is collected through literature studies, observations, interviews, documentation, and Focus Group Discussion (FGD). Result. The results of the research are as follows: The Implementation of E-Government through the Integrated Hajj Computerization System (SISKOHAT) is listed in PMA RI No. 14 of 2012, which is at the heart of the service for pilgrims, as it provides convenience in the registration and input process for pilgrims. Conclusion. E-government through the SISKOHAT application is not optimal, as evidenced by some of the problems and obstacles. The factors that cause the implementation of E-Government through the SISKOHAT Integrated Hajj Computerization System are not optimal. According to Indrajit (2006:15), there are three main elements that must be possessed and seriously considered to achieve success, namely support, capacity, and value. Implementation. Practical efforts to optimize the Implementation of E-Government through the Integrated Hajj Computerization System (SISKOHAT) at the Office of the Ministry of Religion of Cirebon City must be carried out by adding SISKOHAT rooms for pilgrims, developing the quality of human resources by organizing training or various seminars, mentoring prospective elderly pilgrims to make it easier to fill in the terms and conditions that apply to pilgrims